On the organizational structure of multinational firms: Which sourcing mode for which Input? - Verena Nowak; Christian Schwarz; Jens Suedekum (Center for Economic Studies and ifo Institute (CESifo), 2012)
Recent studies indicate that firms often outsource standard and simple tasks, while keeping complex and important inputs inside their boundaries. This observation is difficult to reconcile with the property rights approach of the firm, which suggests that important components should be outsourced in order to properly incentivize the respective suppliers. In this paper we introduce economies of scope into a property rights model where a producer contracts with two suppliers. The organizational decision is driven by two countervailing effects: the ownership rights effect favors outsourcing, while the indirect effect via the suppliers' costs favors vertical integration of both inputs. If production is highly component-intensive, and if one input is much more important than the other, we show that vertical integration of the more important and outsourcing of the less important supplier is chosen in equilibrium. We also consider an open economy setup where the producer decides whether to offshore inputs.
Keywords: D23; F12; L23; 330; multinational firms; outsourcing; intra-firm trade; property rights approach; Multinationales Unternehmen; Beschaffung; Outsourcing; Vertikale Konzentration; Firmeninterner Handel; Eigentumsrechtstheorie; Theorie